Sepolture privilegiate nei monasteri alto medievali ravennati - Novara, Paola (Hortus Artium Medievalium, 2017)
Abstract In Ravenna, the monastic phenomenon came early. The investigations conducted during the nineteenth and twentieth centuries and some materials that are preserved in local museums make it possible to summarize some important considerations regarding the privileged burials in high medieval monasteries. Special attention should be paid to the monasteries of San Vitale and of Santa Maria della Rotonda. The first of the two had been founded at the ancient basilica of S Vitale; the second was founded at the ancient tomb of King Theodoric, transformed into the church of S. Maria della Rotonda or in Faro. Investigations carried out on several occasions in the first half of the twentieth century have identified in the monastery of San Vitale traces of some sepulchral contexts, from which come some important epigrafic claims. The same goes for S. Maria della Rotonda.